2012
DOI: 10.1210/jc.2012-2627
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of 3-Epi-25-OH-D3 during Hypervitaminosis D in Clinical Practice

Abstract: The relative contribution of 3-epi-25-D(3) was not significantly altered during hypervitaminosis D, although the absolute levels reached in serum may be biologically relevant. From a clinical viewpoint, although the small size of the group may affect the lack of relationships, the presence of 3-epi-25-OH-D(3) was apparently unrelated to serum markers of renal and liver function, acute-phase reactants, PTH, and the presence of hypercalcemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…However, 2 large cross-sectional population studies, the US Atherosclerosis Risk in Communities Study [ARIC; n = 13,108 (33)] and the Irish NANS [n = 1122 (34,35)], recently published vitamin D metabolite data. We found a strong correlation between 25(OH)D 3 and C3-epi-25(OH)D 3 consistent with previous findings (34,36,37), although some studies, including ARIC, showed weaker (33,38,39) or no correlation (40). The metabolites 25(OH)D 3 and C3-epi-25(OH)D 3 showed similar demographic patterns compared with total 25(OH)D. Concentrations of C3-epi-25(OH)D 3 were detected in 86% of the population, but its detection frequency and concentrations were higher in children than in older age groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, 2 large cross-sectional population studies, the US Atherosclerosis Risk in Communities Study [ARIC; n = 13,108 (33)] and the Irish NANS [n = 1122 (34,35)], recently published vitamin D metabolite data. We found a strong correlation between 25(OH)D 3 and C3-epi-25(OH)D 3 consistent with previous findings (34,36,37), although some studies, including ARIC, showed weaker (33,38,39) or no correlation (40). The metabolites 25(OH)D 3 and C3-epi-25(OH)D 3 showed similar demographic patterns compared with total 25(OH)D. Concentrations of C3-epi-25(OH)D 3 were detected in 86% of the population, but its detection frequency and concentrations were higher in children than in older age groups.…”
Section: Discussionsupporting
confidence: 92%
“…Skin cells showed the C3-epimerization pathway (48), and the skin of mice fed diets containing cholecalciferol contained up to 20% of 25(OH)D 3 as the C3-epimer (49). To date, little to no C3-epimer has been found in vitamin D supplements (36,39,45), and C3-epimers of cholecalciferol or its metabolites have not been reported in foods.…”
Section: Discussionmentioning
confidence: 99%
“…It is now known that 25(OH)D undergoes epimerization during metabolism, and the 3-epi-25(OH)D 3 of 25(OH)D 3 is most prevalent, forming 3-epi-25-hydroxyvitamin D 3 (3-epi-25(OH)D) (Singh et al 2006). Significant blood concentrations of the 3-epi-25(OH)D 3 have been found in infants (Singh et al 2006; Stepman et al 2011; Granado-Lorencio et al 2012), and, more recently, in adults (Lensmeyer et al 2012; Engelman et al 2014; Cashman et al 2014; Lutsey et al 2015). However, the 3-epi-25(OH)D 3 is not routinely measured, and without chromatographic resolution, it could be mistakenly reported as 25(OH)D 3 because of their identical molecular weights (Lensmeyer et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The cases of hypervitaminosis D usually occur in excessive supplementation. ( 3 , 7 , 8 ) The upper limit of daily vitamin D intake needed to cause toxicity is unknown; however, up to 10,000IU per day was considered safe in a healthy population. ( 3 )…”
Section: Discussionmentioning
confidence: 99%